Effects of varying injector opening pressure on the performance of a B20 JOME biodiesel fueled diesel engine / S. Jaichandar...[et al.] - S., Jaichandar; D., Samuelraj; Kumar, M. Sathish (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
The present work examines the influence of Injector Opening Pressure (IOP) on Jatropha oil fueled Compression Ignition (CI) engine. A Direct Injection (DI) type diesel engine was tested with a blend of 20% Jatropha Oil Methyl Ester (JOME) with 80% diesel (B20) on volume basis. The engine was run on four different injector opening pressures viz. 190, 210, 220 and 230 bar along with standard IOP of 200 bar. For all IOPs, performance considerations like brake thermal efficiency (BTE), brake specific fuel consumption (BSFC), combustion factors such as cylinder pressure and ignition delay and emission issues such as CO, UBHC, smoke opacity and oxides of nitrogen (NOx) were investigated. From the experimental examinations it was observed that IOP of 220 bar showed improvement in terms of BTE and BSFC by about 2.3% and 4.4%. Considerable enhancement in reduction of emission levels particularly for CO, UBHC and smoke were also observed for increased IOP of 220bar by about 26.4%, 12.96% and 3.4% respectively, compared to the engine operated at standard IOP of 200 bar. However, NOx emission level was deteriorated compared to normal IOP. It was also found that increasing the IOP, lowered ignition delay and increased the in-cylinder pressure.